ASPECTS ACTION CRIMINAL IN ENCROACHMENT EX HGU LAND BY THE COMMUNITY - Abdul Azis Manurung; Alfiandi Wisudawansyah Nasution; Syafrizal; Ismail; Sofian (PT. Radja Intercontinental Publishing, 2026)
Encroachment land former Right to Cultivate (HGU) is problem complex laws​ Because involving aspect law criminal law​ agrarian , administration land , as well as conflict social between society , companies , and government . Research This aim For analyze aspects action criminal in control and encroachment land former HGU by the community in the Regency Asahan , North Sumatra, and identify form accountability criminal offenses that can be applied . Research use method law juridical normatively supported​ approach empirical . Data obtained through studies to regulation legislation , documents land , decision court , as well as interview with apparatus enforcer law , agency land , government areas and communities that control land former HGU. Research results show that mastery land former HGU not in a way automatic can qualified as action criminal encroachment land . Determination element criminal must based on the clarity of the rights status on land , expiry of HGU validity period , return process land to the state, the existence of right other legitimate parties , as well as element intent and action oppose law . Form action potential criminal offenses happen covering enter or control land without permit , forgery document land , destruction , threats , violence and actions obstruct implementation decision or policy government . However , the use of law criminal must done in a way carefully and placed as effort final Because part conflict sourced from ambiguity administration , inequality mastery land , and demands redistribution land by the community . Completion case need coordination between government area , office land , apparatus enforcer law , companies and society through land status verification , mediation , reform agrarian , as well as enforcement the law that provides certainty , justice and protection for all over party .